Improved Audit-based malevolent Node Detection and Energy Efficiency for Healthcare Applications (Indian Journal of Public Health Research & Development, 2020)
Recently Wireless Body Area Sensor Networks (WBANs) are going more democratic and have revealedgreat possible in real time supervising of the human body. WBANs have involved a wide range of supervisingapplications for example sports activity, healthcare, and psychotherapy systems. However, WBANs containsmore challenging issues should be resolved such as Quality of Service (QoS), energy efficiency and securityand privacy issues are the most significant concerns. Because these systems manage life-critical data, theymust be secure. To overcome the above issues, Improved Audit-based Malevolent Node Detection forHealthcare Applications is proposed. Audit-based malevolent Detection (AMD) is proposed for discoveringand separating malevolent nodes in WBANs. The AMD system incorporates reputation management,trustworthy route discovery, and recognition of malevolent nodes based on behavioral audits. It integratesthree critical functions: reputation management, route discovery, and identification of malevolent nodesvia behavioral audits. An AMD can build paths consisting of highly entrusted nodes, subject to a desiredpath length constraint. In addition, the node fitness function is utilized for improving the energy efficiencyin WBAN. The simulation result shows that AMD_EE successfully avoids malevolent nodes, even when alarge portion of the network drops to forward packets and enhance the lifetime.
Keywords: Malevolent node detection, trustable routing, Reputation System, Energy Efficiency, Wireless Body Area Network.